Development of practical activity experience for pupils with moderate and severe retardation of mental development - Ilga Prudņikova (Social Welfare: Interdisciplinary Approach)
Modern epoch poses its own demands for special education, because provision of special education needs into inclusive environment is one of the prior courses of education policy in Latvia. The author of the research reveals discrepancy between politically stated progress and school practice in Latvia. Topicality of the research fortifies the necessity to advance pedagogical integrity of pupils with moderate and severe retardation of mental development (RMD). Research includes: analysis of education potential provision in legislation, investigation of theory regarding retardation of mental development, analysis of pedagogic process at special primary boarding school, model of the development of practical activity experience for pupils with moderate and severe RMD at special primary boarding school. As a result of theory analysis – model of the development of practical activity experience for pupils with moderate and severe RMD has been established. Empiric investigation of the development of practical activity experience for pupils with moderate and severe RMD has been done, using the form of quantitative methods investigation in order to examine effectiveness of the established model of the development of practical activity experience.